OUTPATIENT ENDOMETRIAL BIOPSY WITH PIPELLE Vs DIAGNOSTIC DILATATION AND CURETTAGE - Rauf, Raazia; Shaheen, Asma; Sadia, Shamsunisa; Waqar, Faressa; Zafar, Shamsa; Sultana, Saadia; Waseem, Shumaila (Journal of Ayub Medical College Abbottabad, 2014)
Background: Pipelle is a silastic curette which does not require a tenaculum or straightening of the cervical fundus axis because of its flexibility and does not require general anaesthesia. whereas Dilatation and curettage (D&C) requires hospitalization and general anaesthesia along with the problem of postoperative pain. The objective of the study was to assess the effectiveness of Pipelle sampling in terms of adequate specimen collection and patients’ knowledge and perception about Pipelle and compare it D&C. Methods: In this randomized control trial, 203 women presenting with abnormal uterine bleeding were enrolled. The patients were randomly assigned to one of the two procedures. In group A 102 patients were subjected to Pipelle endometrial sampling and in group B 101 patients were enrolled for D&C. Frequencies of adequacy of histopathology reports and cost effectiveness of both groups were compared. Patient’s knowledge, perception, pain and acceptability of the procedure of both groups were also assessed and compared. Results: The mean age of the patients was 46.3±4.45 years. Tissue obtained for histopathology was 100% adequate when the procedure was D&C while it was 98% in Pipelle group. In group-A 92% patients experienced no discomfort, with only 2% experiencing severe pain and 6% mild pain. On the other hand in group-B, 45% patients experienced moderate and 5% experienced severe pain up to 9 on visual analogue scale (VAS) postoperatively and requiring post-operative analgesia. The acceptability for the Pipelle suction curette was 98% and for the D&C group was 34%. Regarding previous knowledge of procedure none of patients (100%) knew about Pipelle procedure but 98% patients were aware of D&C procedure. Pipelle was eight times more cost effective as compared to D&C. Conclusions: The results of obtained by endometrial sample by Pipelle and D&C are compareable. Pipelle significantly produced less pain than D&C. Keywords: Pipelle, suction curette, dilatation and curettage, pre-menopause, visual analogue scale